Women’s Bodies and Emotions: Desertion, Illegitimacy and the Cambridge Union Workhouse in the late Victorian period. - Romero-Ruiz, María Isabel (My University, 2023)
Cambridge Union Workhouse was built a mile away from the city, surrounded by fields to avoid any interference with members of the University or with commercial life. The site was located at 81A, Milton Road, quite close to where the railway station was later built in 1845. On many occasions the workhouse became a necessity rather than a place of temporary relief for women. At difficult times because of unemployment or because of the need for medical assistance in cases of illness (venereal disease) or pregnancy, the workhouse represented the only possibility for survival for many women, among whom there were many prostitutes. Also, single mothers or deserted mothers got a foothold in the workhouse as they were provided with help and support when they found themselves and their children with no other place to go. Illegitimate births provoked disapproval among overseers and boards of guardians as single mothers were considered ‘fallen women’ and the personification of immorality. Unions were allowed to seek affiliation orders against the fathers of illegitimate children being beneficiaries of poor relief within their walls. Also, abandoned wives and mothers were an important part of the workhouse population. There are several examples of cases of this kind in the archives of the Cambridge Poor-Law Union. Therefore, the aim of this paper is to prove that Victorian poor women resorted to the workhouse in situations of vulnerability and precarity because of their condition as ‘fallen’ and because of men’s lack of responsibility towards their wives and children. Consequently, their bodies and emotions were just carriers of stigma. In this sense, the Cambridge Poor Law Union was an example of an institution in Cambridge that formed part of the city’s architecture of containment of immorality and of working-class women’s makeshift economy in the last decades of the nineteenth century.
Keywords: Mujeres - Situación social - S. XIX - Gran Bretaña; Desertion; Illegitimacy; Fallen woman; Workhouse; Victorian